Efektivitas Program Bantuan Langsung Tunai-Dana Desa ( BLT-DD ) Di Desa Sungai Beras Hilir Kecamatan Lubuk Batu Jaya Kabupaten Indragiri Hulu - Isnaini Nur Jannah; Zulkarnaini Zulkarnaini (Peneliti.net, 2023)
Village Fund Direct Cash Assistance (BLT-DD) is one of the programs issued by the Indonesian government to overcome the impact of economic factors on people affected by the Covid 19 pandemic in the form of financial assistance provided to the poor. This study aims to determine the effectiveness of the Village Fund BLT Program in Sungai Beras Hilir Village, Lubuk Batu Jaya District, Indragiri Hulu Regency and to determine the obstacles that hinder the effectiveness of the Village Fund BLT program in Sungai Beras Hilir Village, Lubuk Batu Jaya District, Indragiri Hulu Regency. The theory used in this study is the Theory of Program Effectiveness by Budiani using 4 indicators, namely Program Accuracy, Program Outreach, Program Objectives, and Program Monitoring. This study used a qualitative research type, the necessary data were obtained through observation, interviews and documentation which were then analyzed. The results of this study indicate that first, the determination of targets in providing BLT-DD to recipient communities has not been effective because the village government has not yet been optimal in setting the target criteria for the BLT-DD program. other than that only indicators of program monitoring are already running well, while indicators of program socialization, program objectives which can be concluded are not yet effective. The two obstacles encountered in the effectiveness of the Village BLT-DD program in Sungai Beras Hilir Village, Lubuk Batu Jaya District, Indragiri Hulu Regency were weak data verification/validation and the attitude of program implementers. The local government needs to increase the understanding of a program by implementers, in order to achieve an understanding of an effective program